Enhancing Cancer Treatment Through Combined Approaches: Photodynamic Therapy in Concert with Other Modalities - Gyeong Hong; Ji-Eun Chang (MDPI AG, 2024)
This review explores the role of photodynamic therapy (PDT) as an adjunctive treatment for cancers, with a focus on its potential to enhance the effects of established therapies like chemotherapy, surgery, and radiotherapy. Given the limitations of conventional cancer treatments, PDT's ability to improve therapeutic outcomes through combination strategies is examined. In cancers such as lung, breast, cholangiocarcinoma, and cervical, PDT shows promise in enhancing response rates, reducing recurrence, and minimizing adverse effects when used alongside standard modalities. This study highlights current findings on PDT's mechanisms in complementing chemotherapy, augmenting surgical precision, and enhancing radiotherapeutic effects, thus offering a multi-faceted approach to cancer treatment. Additionally, insights into the clinical application of PDT in these cancers emphasize its potential for reducing tumor resistance and supporting more effective, personalized care. By providing an overview of PDT's synergistic applications across diverse cancer types, this review underscores its emerging significance in oncology as a tool to address traditional treatment limitations. Ultimately, this review aims to inform and inspire researchers and clinicians seeking to refine and innovate cancer therapy strategies through PDT integration, contributing to the advancement of more effective, synergistic cancer treatments.